'Free' children from the cyberworld - Abdul Razak, Mohd. Abbas (New Straits Times Press (NSTP), 2015)
Childhood is a stage where children express ideas, are curious, have fantasies and engage in exciting activities. As they pass through this stage once in a lifetime, parents, teachers and society should provide an environment that is conducive for children to learn all that is good and morally acceptable, and to avoid the unpleasant. During this period, too, children learn an enormous amount of new things through parental guidance, role-modelling, books and play, and by exploring the environment. Adequate attention and proper guidance by parents and others in this crucial phase are potent to inculcate good moral values, discipline, good character, and creative and positive thinking in children as growing adults. Traditionally, all communities, be they in the East or West, have earnestly paid attention to the many vital needs of a child. This attention is given in the hope that later in life, the child will blossom into a good and holistic person. As an individual, he or she will be a responsible person towards him or herself, the community and the nation at large.